The Urgency of Policy Formulation in the Criminalization of Online Gambling: Urgensi Kebijakan Formulasi dalam Tindak Pidana Judi Online - Wong, Sherryl Naomi; Adhari, Ade (Universitas Muhammadiyah Sidoarjo, 2026)
The rapid advancement of digital technology has transformed traditional forms of crime into sophisticated cyber-based offenses, including online gambling, which has become increasingly prevalent in Indonesia. Specifically, the application of Article 303 of the Criminal Code—designed for conventional, physical gambling—proves inadequate for addressing the borderless, anonymous, and technologically complex nature of digital gambling. The knowledge gap lies in the absence of explicit legal provisions regulating online gambling, resulting in inconsistent interpretations, reliance on prohibited analogical reasoning, and weakened legal certainty. This study aims to analyze current punishment practices for online gambling and assess the urgency of reformulating criminal law policies that align with contemporary technological realities. The results reveal that enforcement often stretches Article 303 beyond its intended scope, violating the principle of legality and producing ineffective sanctions that fail to reflect the social and economic harms of digital gambling. The novelty of this research lies in its integrated evaluation of doctrinal deficiencies, judicial practices, and theoretical foundations of criminalization within Indonesia’s evolving cybercrime landscape. The implications underline the urgent need for explicit statutory regulation of online gambling to ensure legal certainty, enhance law-enforcement effectiveness, and strengthen societal protection in the digital era. Highlights: Online gambling grows rapidly while outdated laws fail to regulate digital mechanisms. Applying Article 303 KUHP to cyber-based gambling often violates the legality principle. Urgent legal reform is needed to ensure clarity, effectiveness, and proportional sanctions. Keywords: Online Gambling, Criminal Policy, Legality Principle, Cybercrime Regulation, Legal Reform